The application of restorative justice in China’s environmental crime: an evolutionary game perspective - Zhang, Xinrui (Crime, law and social change, 2024)
The promotion of the restorative justice (RJ) concept has brought significant changes to China's environmental criminal justice system. However, the lack of empirical study makes it hard to support the existing normative arguments and jurisprudential analysis of environmental RJ practices in China. This study aims to investigate the evolutionary mechanisms of the RJ application in environmental crimes. To achieve this goal, a tripartite evolutionary game model comprising the judiciary, the offenders, and the victims, is established based on evolutionary game theory (EGT). Simulations based on 2022 China's environmental criminal justice data indicate that top-down environmental RJ reforms will face resistance due to insufficient public participation. To reverse this situation, we merge sensitivity analyses of model parameters with critical examinations of classical RJ theories. By analyzing the current status and future scenarios of RJ in China's environmental criminal justice, we suggest that: (1) Maintaining moderate penal intensity is the evolution-stable condition for the offenders to develop an intrinsic legal motivation to repair the environment. (2) To ensure both efficiency and fairness, the use of RJ should be determined based on the statutory length of sentences for environmental offenses. (3) Support for victims should be strengthened to increase their benefits from environmental RJ and reduce their legal costs. This paper is innovative in quantitatively evaluating the evolutionary mechanisms of the RJ application by using EGT, which adds to the body of knowledge on RJ conducted by qualitative research. The findings based on EGT can provide an answer to the persistent debate about the relationship between RJ and traditional justice (TJ). While the argument for replacing TJ with RJ may seem attractive, it is not feasible. Considering cost-benefit limitations, incorporating RJ into TJ could achieve positive outcomes in environmental crime.